2017
DOI: 10.2109/jcersj2.16313
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel coral-like Ag<sub>3</sub>PO<sub>4</sub> microspheres under the aid of trisodium citrate and acetic acid

Abstract: Based on a sonochemical route, the effect of trisodium citrate and acetic acid, which served as the structure-directing agents, on the synthesis of Ag 3 PO 4 nano/micro structures was investigated. It is found that the sample prepared at n(AgNO 3 ) = 3 mmol, n(KH 2 PO 4 ) = 2 mmol, n(Na 3 Cit) = 1 mmol and n(CH 3 COOH) = 3 mL is composed of coral-like microspheres. When varying the contents of reagents to other levels or in the absence of acetic acid, it brings about the formation of mesoporous microspheres or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The PXRD patterns of the binary composites AP-Zr-BDC and CN-Zr-BDC evidenced the presence of Zr-BDC in both composites. The crystalline phase AP in the binary composite AP-Zr-BDC does not correspond to the most common cubic Ag3PO4 [34] phases but matches well with silver phosphate found elsewhere [45]. To the contrary, no peak representing CN component in CN-Zr-BDC system was observed (Fig.…”
Section: Synthesis Of Zr-bdc and Its Composites With G-c3n4 And Ag3po4supporting
confidence: 72%
“…The PXRD patterns of the binary composites AP-Zr-BDC and CN-Zr-BDC evidenced the presence of Zr-BDC in both composites. The crystalline phase AP in the binary composite AP-Zr-BDC does not correspond to the most common cubic Ag3PO4 [34] phases but matches well with silver phosphate found elsewhere [45]. To the contrary, no peak representing CN component in CN-Zr-BDC system was observed (Fig.…”
Section: Synthesis Of Zr-bdc and Its Composites With G-c3n4 And Ag3po4supporting
confidence: 72%
“…For Ag 3 PO 4 sample, all diffraction peaks can be indexed according to the standard diffraction lines in the JCPDS card no. 006-0505, implying the formation of pure Ag 3 PO 4 cubic phase [31]. For the composites, the XRD patterns can be indexed into two sets of diffraction peaks corresponding to Bi 4 Ti 3 O 12 and Ag 3 PO 4 phases.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, silver orthophosphate (Ag 3 PO 4 ) with a bandgap energy of ~ 2.4 eV has been extensively studied as a promising visible light photocatalyst [1231]. First principle calculations based on the density functional theory suggested that Ag 3 PO 4 has a highly dispersive band structure of the conduction band minimum resulting from Ag s -Ag s hybridization without localized d states [32], which is advantageous for the separation of electron hole pairs as well as the electron transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The modifications of morphology in Ag3PO4 photocatalyst have been applied to improve their photocatalytic activity [6]. Morphology of coral-like microspheres [7], branched Ag3PO4 crystals with porous structure [8] and truncated tetragonal bipyramids [9] had improved the photocatalytic activity of Ag3PO4. The changed morphology can influence the activity due to a different facet of Ag3PO4.…”
Section: Introductionmentioning
confidence: 99%